Implementation of Digital Whiteboard Technology to Improve User Interaction in Lecture Halls A101 - Maruli Darusman Marpaung; Dimas Maulana Akbar; M. Rasinu Putra; Hery Irwan (TeIKa, 2026)
This study aims to analyze the effectiveness of digital whiteboard technology implementation in enhancing user interaction, particularly in classroom A101 at Universitas Riau Kepulauan. The main issues with conventional whiteboards include limited information storage, lack of remote collaboration, and low flexibility in material delivery. The research employed the Plan-Do-Check-Act (PDCA) method, covering need identification, device installation, calibration, trial, and evaluation. The findings indicate that the digital whiteboard improves students’ concentration, engagement, and collaboration in the learning process. Moreover, it supports teaching efficiency, multimedia integration, and provides a more interactive learning experience. The main challenges identified were user training needs and dependency on technological infrastructure. Overall, the implementation of digital whiteboards proves superior to conventional methods in creating effective, efficient, and collaborative learning.